Heat-Induced Oxidation of the Nuclei and Cytosol - Babbar, Richa; Karpinska, Barbara; Grover, Anil; Foyer, Christine H. (Frontiers in Plant Science, 2021)
The concept that heat stress causes a large accumulation of reactive oxygen species (ROS) is widely accepted. However, the intracellular compartmentation of ROS accumulation resulting from heat stress remains poorly characterized. We therefore used redox-sensitive green fluorescent protein (roGFP) to provide compartment-specific information on heat-induced redox changes of the nuclei and cytosol of Arabidopsis leaf epidermal and stomatal guard cells. We show that heat stress causes a large increase in the degree of oxidation of both compartments, causing large shifts in the glutathione redox potentials of the cells. Heat-induced increases in the levels of the marker transcripts, heat shock protein (HSP)101 and ascorbate peroxidase (APX)2 were maximal after 15 minutes of the onset of the heat treatment. RNAseq analysis of the transcript profiles of the control and heat-treated seedlings revealed large changes in transcripts encoding HSPs, mitochondrial proteins, transcription factors and other nuclear localised components. We conclude that heat stress causes extensive oxidation of the nucleus as well as the cytosol. We propose that the heat-induced changes in the nuclear redox state are central to both genetic and epigenetic control of plant responses to heat stress.